A new species of the genus Sazonia O. Gorbunov & Arita, 2001 from Vietnam (Lepidoptera: Sesiidae) - Gorbunov, Oleg G.; Arita, Yutaka (Zootaxa, 2018)
A new clearwing moth species of the tribe Osminiini is described and illustrated from North Vietnam: Sazonia (Sazonia) vietnamica sp. nov. The female and the larval host plant are unknown. The genus Sazonia is recorded for the country for the first time. The holotype is deposited in the collection of the National Museum of Nature and Science, Tsukuba (formerly the Natural Science Museum Tokyo).